2003
DOI: 10.3354/meps254069
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the invasive, nonindigenous seagrass Zostera japonica on nutrient fluxes between the water column and benthos in a NE Pacific estuary

Abstract: The effects of Z. japonica on dissolved nutrient fluxes between the water column and the benthos in Yaquina Bay, Oregon, USA were examined. Nutrient fluxes in Zostera japonica habitats were compared to those in adjacent unvegetated sediment in warm and cool seasons, and in daylight and darkness. In daylight, Z. japonica habitats were net sinks for nitrate (NO 3 ), ammonium (NH 4 ) and dissolved reactive phosphorus (DRP) in the warm season, and for NO 3 and DRP in the cool season. At night in the warm season, Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 40 publications
(49 reference statements)
0
49
1
Order By: Relevance
“…2) is a macro-tidal drowned-river estuary located on the central Oregon coast of which about 60 % of the area is intertidal (Larned 2003). The estuary area is roughly 11.5 km 2 in a drainage basin about 445.6 km 2 reported by multiple sources (Choi 1975;Sigleo and Frick 2007).…”
Section: Study Areamentioning
confidence: 99%
“…2) is a macro-tidal drowned-river estuary located on the central Oregon coast of which about 60 % of the area is intertidal (Larned 2003). The estuary area is roughly 11.5 km 2 in a drainage basin about 445.6 km 2 reported by multiple sources (Choi 1975;Sigleo and Frick 2007).…”
Section: Study Areamentioning
confidence: 99%
“…To date, only a handful of studies have measured the effects of invasive species on the cycling and storage rates of carbon and nitrogen in coastal systems (e.g., Larned 2003;Ruesink et al 2005Ruesink et al , 2006Tyler et al 2007;Williams and Smith 2007 for introduced seaweeds). Examples from the invasion of Spartina (see above) have shown that Spartina can significantly affect macroalgal production, increase storage of carbon and nitrogen in plant detritus, and cause a shift from a net autotrophic to a net heterotrophic system (Tyler and Grosholz, in review).…”
Section: Effects On Communities and Ecosystemsmentioning
confidence: 99%
“…In addition, Willapa's introduced engineers probably also affect biogeochemical cycles. In another coastal estuary, introduced Zostera japonica serves as a sink for water-column nutrients (Larned 2003), and bivalves can store nutrients in biodeposits (Chapelle et al 2000), or, at high densities, enhance nutrient release (Bartoli et al 2001). Furthermore, oyster expansion has occurred at the expense of burrowing shrimp and other infauna, undoubtedly causing changes in sediment porosity and bioturbation and further affecting biogeochemistry (Webb & Eyre 2004).…”
Section: Primary and Secondary Production In Heavily Invaded Estuariesmentioning
confidence: 99%